Repurposing of dipeptidyl peptidase FDA-approved drugs in Alzheimer's disease using network pharmacology and in-silico approaches - Roney, Miah; Uddin, Md. Nazim; Khan, Azmat Ali; Fatima, Sabiha; Mohd Fadhlizil Fasihi, Mohd Aluwi; Hamim, S.M. Istiaque; Ahmad, Asrar (Elsevier Ltd, 2025)
Type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD) have similar clinical characteristics in the brain and islet, as well as an increased incidence with ageing and familial susceptibility. Therefore, in recent years there has been a great desire for research that elucidates how anti-diabetic drugs affect AD. This work attempts to first elucidate the possible mechanism of action of DPP-IV inhibitors in the treatment of AD by employing techniques from network pharmacology, molecular docking, molecular dynamic simulation, principal component analysis, and MM/PBSA. A total of 463 targets were identified from the SwissTargetPrediction and 784 targets were identified from the SuperPred databases. 79 common targets were screened using the PPI network. The GO and KEGG analyses indicated that the activity of DPP-IV against AD potentially involves the hsa04080 neuroactive ligand-receptor interaction signalling pathway, which contains 17 proteins, including CHRM2, CHRM3, CHRNB1, CHRNB4, CHRM1, PTGER2, CHRM4, CHRM5, TACR2, HTR2C, TACR1, F2, GABRG2, MC4R, HTR7, CHRNG, and DRD3. Molecular docking demonstrated that sitagliptin had the greatest binding affinity of − 10.7 kcal/mol and established hydrogen bonds with the Asp103, Ser107, and Asn404 residues in the active site of the CHRM2 protein. Molecular dynamic simulation, PCA, and MM/PBSA were performed for the complex of sitagliptin with the above-mentioned proteins, which revealed a stable complex throughout the simulation. The work identifies the active component and possible molecular mechanism of sitagliptin in the treatment of AD and provides a theoretical foundation for future fundamental research and practical implementation.